The Environmental Data Initiative: Connecting the past to the future through data reuse. Issue 1 (6th January 2023) - Gries, Corinna; Hanson, Paul C.; O'Brien, Margaret; Servilla, Mark; Vanderbilt, Kristin; Waide, Robert
Abstract: The Environmental Data Initiative (EDI) is a trustworthy, stable data repository, and data management support organization for the environmental scientist. In a bottom‐up community process, EDI was built with the premise that freely and easily available data are necessary to advance the understanding of complex environmental processes and change, to improve transparency of research results, and to democratize ecological research. EDI provides tools and support that allow the environmental researcher to easily integrate data publishing into the research workflow. Almost ten years since going into production, we analyze metadata to provide a general description of EDI's collection of data and its data management philosophy and placement in the repository landscape. We discuss how comprehensive metadata and the repository infrastructure lead to highly findable, accessible, interoperable, and reusable (FAIR) data by evaluating compliance with specific community proposed FAIR criteria. Finally, we review measures and patterns of data (re)use, assuring that EDI is fulfilling its stated premise. Abstract : The Environmental Data Initiative (EDI) is a trustworthy, stable data repository, and data management support organization for the environmental scientist providing tools and support that allow the environmental researcher to easily integrate data publishing into the research workflow. We discuss how comprehensive metadata and the repository infrastructure lead to highly findable, accessible, interoperable, and reusable (FAIR) data by evaluating compliance with specific community proposed FAIR criteria and review measures and patterns of data (re)use, assuring that EDI is fulfilling its stated premise.